Advanced Transmission Electron Microscopy Applications to Nanomaterials - Deepak, Francis Leonard; Mayoral, Alvaro; Arenal, Raul (Springer International Publishing : Imprint: Springer, 2015)
This book highlights the current understanding of materials in the context of new and continuously emerging techniques in the field of electron microscopy.  The authors present applications of electron microscopic techniques in characterizing various well-known & new nanomaterials. The applications described include both inorganic nanomaterials as well as organic nanomaterials.